Micronutrient deficiency effect on the nutritional status of the castor bean cultivar Iris - Lange, Anderson; Martines, Alexandre Martin; Silva, Marcos Antonio Camacho da; Sorreano, Maria Claudia Medes; Cabral, Cleusa Pereira; Malavolta, Eurípedes (Pesquisa Agropecuaria Brasileira, 2005)
The objectives of this work were to characterize the visual symptoms of micronutrient deficiencies, and their effects on nutricional status of castor beans. A greenhouse experiment with nutrient solutions was carried out from February to June, 2003. The commercial hybrid "Iris" was used. Treatments were as follows: complete, minus B, minus Cu, minus Fe, minus Mn, minus Mo, and minus Zn. Symptoms of deficiency were observed in the treatments with omission of B, Fe, and Mn. The symptoms firstly developed when either Fe or Mn was deficient, and they were followed by those deficient in boron. Dry matter yield was affected in the decreasing order: Fe>Mn>B. Both upper and lower leaves reflect the nutritional status of the castor bean with respect to B, Cu, Fe, Mn, Mo and Zn. Leaf chlorophyll, as measured in units SPAD, was influenced by the treatments.